Mr. Murder [compact disc, unabridged] - Koontz, Dean R. (Dean Ray), 1945- (Simon & Schuster Audio, 1993)
A madman wages a terrifying campaign to eliminate mystery writer Marty Stillwater when he claims he's the real Marty Stillwater.